Underground quarries in the area of Agiades, Samos Island, Greece: Notes on historical topography and chronology - Tziligkaki, Eleni; Stamatakis, Michael (Bulletin of the Geological Society of Greece, 2018)
This paper shows the need for cataloguing and comparing tool marks left on the quarries’ front in order for the chronological sequence of the different phases of limestone exposed in underground quarries at Agiades, Chora Samos, to be assessed. Up to now, an archaic and a roman phase of exploitation is inferred by surface pottery, tools, tool marks, the monuments themselves, and parallels from underground quarries on the island of Crete. The proximity of the quarries to a temenos of Apollo and the Nymphs is comparable to other cases from the Greek world. In an attempt to understand the social status of the quarrymen and their level of literacy, data from the graffiti observed in Eupalinos’ tunnel were correlated with the lack of patronym and ethnonym observed in quarries in the Aegean, and related to the characterization of the Samians as «πολυγράμματοι». A control of Hera’s sanctuary over the quarries at Agiades is implied by the frequent appearance of the letters HP on slabs used in Eupalinos’ tunnel.